An infant with truncus arteriosus with situs inversus with single atrium: A case report. Issue 3 (March 2017) - Kumar, Parveen; Devi, A.; Ghosh, Gopal
Abstract: Truncus arteriosus is a rare heart defect comprising <1% of congenital cyanotic heart disease. Rarely it may be associated with single ventricle, but association with single atrium is very rare. We report a case of truncus arteriosus (Van Praag type A2) with single atrium and single ventricle. <Learning objective: In our case truncus arteriosus was associated with single atrium, single ventricle, and situs inversus which is rare and has not been reported in the literature.>